Effectiveness Of Training Program in Movenpick Resort & Spa Jimbaran: An Evaluative Study - I Gusti Ayu Putu Wita Indrayani; Komang Ari Herlia Listianti (International Journal of Applied Research in Tourism and Hospitality, 2022)
Training is one area of Talent Management practice which is implemented in most organizations and has been shown to improve service quality in 5-star hotels. Nevertheless, assessment of training programs is rarely undertaken in real-world situations. The purpose of this research is to assess the effectiveness of the training program using Kirkpatrick's theory and model. To achieve the purpose, this research adopted mixed method analysis through survey design using questionnaires and validated through in-depth interviews with Talent and Culture Manager. Implementing stratified proportioned sampling from 307 employees, the sample of this research is 75 employees representing all departments. The results indicate that the training program incorporates Kirkpatrick's theory of training effectiveness into good scores and is provided with a range of strategies to perpetually establish an effective training program. The findings of this study contribute to providing an overview of hotel and Talent & Culture management in order to emphasize the basics of an effective training program and its evaluation for the quality of hotel success. It also contributes to literature by expanding on how to assess the training program in the hotel and what practical features should be addressed.